Analisis Implementansi Prinsip Syariah terhadap Pembiayaan Mudharabah pada Bank Syariah Indonesia - Rachmat Sugeng Sugeng; Abdul Majid Bakri (Jurnal Pasar Modal dan Bisnis, 2022)
This study aims to determine how the implementation of sharia principles on mudharabah financing at Bank Syariah Indonesia (BSI) KC Makassar 2. This study uses a qualitative approach that requires a process that comes from the results of observations, interviews and documentation. The results of this study indicate that the implementation of mudharabah financing at Bank Syariah Indonesia (BSI) KC Makassar 2 is not in line with DSN MUI Fatwa No. 07/DSN-MUI/IV/2000 Regarding Mudharabah Financing (Qiradh) but the researchers found the first finding that mudharib who want to apply for financing do not need to include collateral and secondly shahibul maal and mudharib share operational costs.Abstract bahasa Inggris memuat tujuan (purpose), metode (methods), temuan (finding), keterbatasan/implikasi (jika ada) dan originalitas riset/signifikansi riset.